Bridging the competencies gap between quantity surveyors and facilities managers - Md. Salleh, Mohammad Fahmy; Syed Khuzzan Alhabshi, Sh Mazlina; Hashim, Khairusy Syakirin Has-Yun (Penerbit UTHM, 2014)
The construction industry is facing a period of change. The roles of the professions are also changing; including the roles of quantity surveyors. There are opportunities for quantity surveyors to seize the initiative to broaden their involvement in other industries. Facilities management is considered as a bright new venture for quantity surveyors as many big and complex buildings that have been built are now requiring appropriate maintenance management. Organisations nowadays realise the impact of their facilities to achieve the overall organisational objectives. However, in order for quantity surveyors to venture into the facilities management industry, they will have to improve their competencies’ sets and their knowledge bases to fulfil the facilities management competencies’ requirements. This paper reports the preliminary findings on a study examining the competencies gaps of quantity surveyors in order to venture into facilities management. A semi-structured interview technique was conducted with six experienced quantity surveyors who have been actively involved with facilities management consultancies. The findings from the interviews indicated that there are several competencies gaps that need to be overcome by quantity surveyors in order to venture into facilities management, i.e. the knowledge and competence on property maintenance, support services operation and business organisation.